Mangrove Forest Rehabilitation Strategy in Ponelo Kepulauan District, North Gorontalo Regency - Sriwulan Daud; Moch Rio Pambudi; Ramla Hartini Melo (Universitas Negeri Gorontalo, 2026)
Mangrove forests provide essential ecological, economic, and social benefits, including coastal protection, habitat provision, and support for local livelihoods. However, mangrove ecosystems in Ponelo Kepulauan District, North Gorontalo Regency, have experienced significant degradation due to land conversion, illegal logging, coastal abrasion, climate change, and inadequate management. This study aimed to formulate an appropriate mangrove forest rehabilitation strategy based on internal and external factors affecting rehabilitation efforts. A descriptive quantitative approach supported by qualitative data was employed through field observations, interviews with coastal communities and village government officials, and SWOT analysis using the Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) matrices. The results indicate that the rehabilitation strategy is positioned in Quadrant I (Strengths–Opportunities), with an IFAS score of 0.95 and an EFAS score of 1.15, indicating strong internal conditions supported by favorable external opportunities. The recommended strategy emphasizes optimizing the ecological and economic potential of mangroves, strengthening collaboration among local communities, government agencies, universities, and non-governmental organizations, promoting community-based ecotourism, enhancing environmental education, and improving post-planting management and institutional capacity. These integrated strategies are expected to enhance the effectiveness and sustainability of mangrove rehabilitation while supporting environmental conservation and improving the welfare of coastal communities in Ponelo Kepulauan District.